Registros sedimentares e bioestratigráficos da sub-bacia de Icaraí (Ce): processos marinhos e dinâmicas paleoambientais no quaternário da margem equatorial Brasileira - Lins, Jéssica Patrícia Capistrano (2024)
The Quaternary began 2.58 million years ago and is marked by intense climatic changes characterized by alternating glacial and interglacial periods. One of the most reliable materials for studying climate changes is sediments collected from deep oceanic regions. These sediments provide records of Earth's history, allowing for the understanding of climate patterns during the glacial and interglacial periods of the Quaternary. This information enhances our understanding of the interactions between the ocean, atmosphere, and climate system, enabling the prediction of scenarios and events through mathematical modeling. This research aims to identify the sedimentological and biostratigraphic variation of the Quaternary in the Icaraí sub-basin (CE), Brazilian Equatorial Margin, to understand the marine processes and paleoenvironmental dynamics of this period in the region. The study was conducted on four cores collected from the continental slope of the Icaraí sub-basin, which were subjected to sedimentological and micropaleontological analyses. The continental slope of this sub-basin is predominantly composed of fine sediments, with silt being the most abundant fraction and calcium carbonate content ranging from 20.81% to 68.05%. Consequently, the sedimentary facies sandy marl, calcareous marl, and terrigenous mud were identified. These sediments are poorly sorted, exhibiting platykurtic and very platykurtic curves with a tendency toward positive and very positive skewness. The depositional environment is characterized as low-energy. Regarding the biostratigraphic zonation, four biozones and two subzones were identified, representing colder intervals (Biozones W and Y; subzones: Y2 and Y1) and warmer intervals of the Pleistocene (Biozone X) and the Holocene (Biozone Z). The variation in the Pulleniatina plexus enabled the recognition of subzones Y2 and Y1 (A and B). The Z/Y boundary was identified at the 13– 16 cm level of core ANP-1418, yielding a sedimentation rate of 1.64 cm per 1,000 years for the studied area during Biozone Z. Thus, it is believed that sedimentation in the region experienced erosional or non-depositional processes, as most cores lack the portion corresponding to Holocene sedimentation. These results contribute to understanding the sedimentary evolution and paleoenvironmental dynamics of the continental slope of the Icaraí sub-basin, revealing the interaction between climatic and oceanographic changes throughout the Quaternary